2011
DOI: 10.1128/jcm.02144-10
|View full text |Cite
|
Sign up to set email alerts
|

Impact of rpoB Mutations on Reduced Vancomycin Susceptibility in Staphylococcus aureus

Abstract: Of 38 vancomycin-intermediate

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
91
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 111 publications
(93 citation statements)
references
References 22 publications
1
91
1
Order By: Relevance
“…In most, but not all, cases, the relevant mutated genes appear to be directly or indirectly involved with the biosynthesis/metabolism of the staphylococcal cell wall, specifically, two-component sensory regulatory systems controlling the transcription of genes in cell wall synthesis (32,33,43). However, mutations in the RNA polymerase gene rpoB were also detected in VISA isolates (42).…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…In most, but not all, cases, the relevant mutated genes appear to be directly or indirectly involved with the biosynthesis/metabolism of the staphylococcal cell wall, specifically, two-component sensory regulatory systems controlling the transcription of genes in cell wall synthesis (32,33,43). However, mutations in the RNA polymerase gene rpoB were also detected in VISA isolates (42).…”
Section: Introductionmentioning
confidence: 97%
“…In another study, the predominant genetic change was in the yvqF/vraSR system (41), while Watanabe et al showed that most of the 38 VISA strains recovered from 10 different countries carried a mutated rpoB (42). In most, but not all, cases, the relevant mutated genes appear to be directly or indirectly involved with the biosynthesis/metabolism of the staphylococcal cell wall, specifically, two-component sensory regulatory systems controlling the transcription of genes in cell wall synthesis (32,33,43).…”
Section: Introductionmentioning
confidence: 99%
“…59 SEONG, KIM, and KWON alternative drug for the treatment of Gram-positive bacteria including S. aureus due to potent bactericidal activity (Sauermann et al, 2008). Recently daptomycinresistant and vancomycin-intermediate resistant S. aureus was reported to possess single nucleotide polymorphisms (SNPs) in rpoB (Cui et al, 2010;Matsuo et al, 2011;Watanabe et al, 2011). In the present study the poultry multi-drug MRSA strain BP11069 carried a unique SNP, E42K, the function of which was unknown.…”
Section: Discussionmentioning
confidence: 88%
“…The complete rpoB gene sequence (RS) typing is a more economic, informative and alternative method than MLST, and better for subspecies level study (Seong et al, 2012). Some mutations in rpoB confer rifampin, daptomycin and vancomycin resistance in S. aureus (Aubry-Damon et al, 1998;Cui et al, 2010;Watanabe et al, 2011;Wichelhaus et al, 1999). Thus, phylogenetic analysis of S. aureus strains with the complete rpoB gene sequence may provide more information on the resistance to antibiotics which are commonly used in MRSA treatment.…”
mentioning
confidence: 99%
“…The rpoB mutations selected by rifampicin were found to have multiple resistance to both vancomycin and daptomycin by a possible mechanism of increased cell wall thickness and these mutations always were found in VISA strains (39). Meanwhile, rifampicin-resistant strains were found to contain vancomycin resistance (40), and the researchers suggest the rpoB mutations play an important role in vancomycin resistance. These results may give a reason infectious Staphylococcus aureus strains own resistance to penicillin and its derivatives.…”
Section: Present Pathogenic Characteristic Of Mrsamentioning
confidence: 97%